Blood transfusion therapy in patients with vitamin B12 deficiency anemia after resection of 2/3 of the stomach - Madasheva, Anajan Gazkhanovna; Abdiev, Kattabek Makhmatovich (Science and Education, 2023)
This article is devoted to blood transfusion therapy in patients with vitamin B12 deficiency anemia after 2/3 gastrectomy. The article describes the causes of vitamin B12 deficiency in patients, its therapy, methods of blood transfusion therapy in patients with anemia.